2021
DOI: 10.1016/j.xcrm.2021.100394
|View full text |Cite
|
Sign up to set email alerts
|

CCNE1 copy number is a biomarker for response to combination WEE1-ATR inhibition in ovarian and endometrial cancer models

Abstract: Summary CCNE1 -amplified ovarian cancers (OVCAs) and endometrial cancers (EMCAs) are associated with platinum resistance and poor survival, representing a clinically unmet need. We hypothesized that dysregulated cell-cycle progression promoted by CCNE1 overexpression would lead to increased sensitivity to low-dose WEE1 inhibition and ataxia telangiectasia and Rad3-related (ATR) inhibition (WEE1i-ATRi), thereby optimizing efficacy and tolerability. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…Multiple preclinical studies have recently shown that in vitro efficacy of adavosertib does not directly translate into clinical responses to WEE1 inhibition in unselected patient populations. Importantly, increased CCNE1 expression has been consistently correlated with clinical response to WEE1 inhibitors ( 32 37 ). Thus, CCNE1 mRNA expression is a patient selection biomarker for WEE1 inhibitor response in patients with cancer at the clinical level.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple preclinical studies have recently shown that in vitro efficacy of adavosertib does not directly translate into clinical responses to WEE1 inhibition in unselected patient populations. Importantly, increased CCNE1 expression has been consistently correlated with clinical response to WEE1 inhibitors ( 32 37 ). Thus, CCNE1 mRNA expression is a patient selection biomarker for WEE1 inhibitor response in patients with cancer at the clinical level.…”
Section: Resultsmentioning
confidence: 99%
“…This assay confirmed the potency boost associated with the 2,6-dimethyl phenol motif of analog 6.compare to both mono methyl analogs 1 and 4. Interestingly, the chloro analogs 17 and 18 without a methyl at R 4 that showed comparable potency in the enzymatic assay (Table 1) were significantly less potent than analog 16 in the cell-based assay despite good cell permeability (analog 17 Caco2 Papp A-B=14.1 x 10 -6 cm/s, efflux ratio (ER) = 1.2; analog 18 Caco2 Papp A-B=18.8 x 10 -6 cm/s, ER=0.4). 2-Chloro phenol analog 16 showed favorable cell potency compared to 2,6-dimethyl phenol analog 6 but such chloro substitution resulted in notable increase in metabolism in a human hepatocyte assay.…”
Section: Compound Structure-activity-relationships and Optimizationmentioning
confidence: 99%
“…3 In contrast, WEE1 phosphorylates tyrosine 15 (Tyr15) of CDK1 and is implicated in the regulation of both CDK1 and CDK2 activity. 4 PKMYT1 function does not appear to be critical in the unperturbed cell cycle whereas WEE1 function is essential for cell cycle progression of cells. 5 However, the absence of functional PKMYT1 in a genetically-vulnerable tumor, such as with CCNE1-amplification, causes cells to lose major checkpoint regulation leading to hyperactive CDK1, unscheduled mitosis and catastrophic DNA damage, ultimately resulting in cell death.…”
Section: Introduction and Biological Rationalementioning
confidence: 98%
See 2 more Smart Citations